Pengembangan Media Pembelajaran Video Tutorial Pada Mata Pelajaran Pemangkasan dan Pewarnaan Rambut di SMK N 7 Padang - Aulia, Suci; Astuti, Murni (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2024)
The background of this research is because of the low student learning outcomes and the lack of maximum results of students' practice on graduation technique hair cutting material due to the learning media that has not varied, the learning media used is still in the form of student activity sheets and not yet structured. The purpose of this study was to develop video-based learning media for hair cutting in the graduation technique at SMK Negeri 7 Padang, to analyze the validity, practicality and effectiveness of video-based learning media for hair cutting in the graduation technique. This type of research is research and development (Research and Development). . The research was conducted at SMK N 7 Padang on 22 May - 27 May 2023. The research subjects were product validation and practicality. 4D model development procedures (Define, Design, Development and Dissemination). The type of data is primary data. Observation and questionnaire data collection techniques. Questionnaire research instrument with a Likert scale. The data analysis technique is descriptive analysis. The results of this study are learning video media that has been developed with the 4-D development model, the validation results for media design are 0.78 with the valid category and for material validation 0.88 with the valid category. Practicality results were obtained from student responses of 84.54% in the very practical category and practicality values ??were obtained from teacher responses of 92.05% in the very practical category. From the acquisition of these results, the learning media based on video learning can be said to be valid and practical to use as teaching materials in class. As for the suggestions that the researchers gave regarding the results of this study, the first is for teachers to be able to use this learning video media as a reference in classroom learning, for students this video media is advised to make good use of this video to improve learning outcomes.